Emergency Services Workforce 2030 - McLennan, Blythe; Chong, Jane; Dunlop, patrick (Bushfire and Natural Hazards CRC, 2022)
Australia’s emergency management sector sits within an environment that is becoming ever more complex, dynamic and uncertain. This is due to factors like a growing population, changing climate, social and cultural change, and the impact of new technologies. At the same time, the nature of how we work, in both paid and voluntary ways, is also changing. Work is greatly influenced by changes in technology and lifestyle, and by increasing levels of interconnectivity and cross-boundary collaboration.